Pollen and spores : applications with special emphasis on aerobiology and allergy - Agashe, Shripad N; Caulton, Eric (Enfield, NH : Science Publishers, 2009)
'The increasing desensitization of human and animal immune systems is due in part to environmental pollution, which is of major concern to medical, veterinary and allied professionals. Airborne particles and chemical compounds are prominent components of the air we breathe and the consequent, sometimes life threatening, ill health suffered.''The authors aim in writing this book is to draw attention to the importance of air spora and the role played in air pollution and the impact on immune systems. Emphasis is on the role of pollen and spores as bioparticles, which penetrate to varying degrees the respiratory system of ourselves and the animals we keep (e.g., farm, zoo and home) causing allergic reactions. The book is designed to be of help both as a source of information and a practical guide to palynology, the study of pollen and spores.'--Jacket.
Introduction; History of Development of Palynology; Pollen Formation Development of Pollen Wall and Tapetum; Pollen Morphology; Pollen Morphological Description of Some Plants; Pollen Morphology of Gymnosperms; Spore Morphology; Morphology of Microfossils; Current Techniques in Palynology; Pollen Physiology (Palynophysiology); Minor Applications of Pollen Studies; Melissopalynology; Aerobiology: Aeropalynology -- Part I; Aerobiology: Aeropalynology -- Part II; Aerobiology -- Applications of Airborne Pollen Studies in Allergy; Significance of Fungi as Aeroallergens; Comprehensive Account of Most Common Aeroallergens and their Source Plants; Pollen Calendars -- Global Scenario; Applications of Aerobiology: Pollen Analysis and Meteorology; Forensic Palynology; Applications of Fossil Pollen Studies.
Includes bibliographical references (pages 355-384) and index.
Keywords: Palynology; Pollen; Respiratory allergy